2007
DOI: 10.1007/s10552-006-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

Meat and dairy consumption and subsequent risk of prostate cancer in a US cohort study

Abstract: Overall, consumption of processed meat, but not total meat or red meat, was associated with a possible increased risk of total prostate cancer in this prospective study. Higher intake of dairy foods but not calcium was positively associated with prostate cancer. Further investigation into the mechanisms by which processed meat and dairy consumption might increase the risk of prostate cancer is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
117
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 22 publications
(24 reference statements)
11
117
0
3
Order By: Relevance
“…Also, observations on high-fat dairy products may be limited in our study because men reported generally low intake of these foods. Our findings of an increased risk with higher calcium intake are consistent with several (11,12,(17)(18)(19)(20), but not all (13,(21)(22)(23)(24), existing studies. Of note, an increased risk of prostate cancer was noted among men with very high calcium intakes (i.e., >1,500 mg/d), which is also consistent with other studies (17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, observations on high-fat dairy products may be limited in our study because men reported generally low intake of these foods. Our findings of an increased risk with higher calcium intake are consistent with several (11,12,(17)(18)(19)(20), but not all (13,(21)(22)(23)(24), existing studies. Of note, an increased risk of prostate cancer was noted among men with very high calcium intakes (i.e., >1,500 mg/d), which is also consistent with other studies (17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…Calcium, a major nutrient in dairy products, has also been associated with increased prostate cancer risk (11,12,(17)(18)(19)(20), although other studies do not support this association (13,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that total meat or red meat intake is not associated with prostate cancer risk is consistent with most previous prospective studies (Snowdon, 1988;Mills et al, 1989;Hsing et al, 1990;Chan et al, 2000;Allen et al, 2004;Cross et al, 2005;Rohrmann et al, 2007), although some found positive associations with red meat (Michaud et al, 2001), hamburgers (Veierod et al, 1997), beef (Le Marchand et al, 1994) or cooked processed meat for either total or advanced prostate cancer. For fish, our results, which are based on a wide range of intake, provide no evidence that intake is associated with risk, and is consistent with most previous studies (Severson et al, 1989;Hsing et al, 1990;Le Marchand et al, 1994;Gronberg et al, 1996;Schuurman et al, 1999), although some have reported a negative (Terry et al, 2001;Augustsson et al, 2003) or positive association (Mills et al, 1989;Allen et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk. An alternative hypothesis is that dairy products may increase prostate cancer risk via their high calcium content, and our finding of a positive association with calcium intake is consistent with some (Chan et al, 2001;Gao et al, 2005;Tseng et al, 2005;Giovannucci et al, 2006;Kesse et al, 2006;Ahn et al, 2007;Mitrou et al, 2007), but not all, prospective studies (Koh et al, 2006;Severi et al, 2006;Rohrmann et al, 2007). It has been suggested that a high calcium intake may increase risk by suppressing the synthesis of 1,25-dihydroxyvitamin D, which has an antitumour effect on human prostatic cells in vitro (Giovannucci, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…Some of them showed a positive association between meat consumption and prostate cancer, especially for well-done and red meat [7,8,9,10], but others reported no association [11,12,13]. The few studies with focus on HCA intake revealed inconsistent results; two studies reported no association [8,10], whereas one study indicated an increasing risk for intake of PhIP [9] and another one an increased risk for MeIQx and DiMeIQx [7].…”
Section: Introductionmentioning
confidence: 99%